Estrogen Deficiency after Menopause Does Not Result in Male Very-Low-Density Lipoprotein Metabolism Phenotype - Magkos, Faidon (The Endocrine Society, 2010)
Context: Sex differences in lipid metabolism result in a less proatherogenic plasma lipid profile in premenopausal women than men. The mechanisms responsible for this are unclear but are thought to be related to differences in the sex hormone milieu in men and women. Objective: Our objective was to evaluate the effect of endogenous sex hormones on very-low-density lipoprotein (VLDL) triglyceride (TG) and apolipoprotein B-100 (apoB-100) metabolism. Experimental Design and Main Outcome Measures: We measured basal VLDL-TG and VLDL-apoB-100 concentrations and kinetics by using stable isotope-labeled tracers. Setting and Participants: Eight premenopausal women [age, 43 ± 8 yr; body mass index (BMI), 35 ± 4 kg/m(2); mean ± sd], eight postmenopausal women (age, 55 ± 4 yr; BMI, 34 ± 4 kg/m(2)), and eight men (age, 41 ± 13 yr; BMI, 34 ± 4 kg/m(2)) were studied at Washington University School of Medicine, St. Louis, MO. Results: VLDL-TG secretion rate was approximately double (P < 0.05) in postmenopausal women and men compared with premenopausal women but not different in postmenopausal women and men. The secretion rate of VLDL-apoB-100 was not different in pre- and postmenopausal women but was greater (P < 0.05) in men than in women. Conclusions: Endogenous ovarian sex steroids are responsible for sexual dimorphism in VLDL-TG secretion, whereas VLDL-apoB-100 secretion is not regulated by female reproductive hormones.